1993
DOI: 10.1111/j.1095-8649.1993.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river red gum, Eucalyptus camaldulensis, litter on golden perch, Macquaria ambigua

Abstract: Aquaria with added river red gum, Eucalyptus camaldulensis, litter became hypoxic, with decreased pH and contained up to 30 mg 1−1 tannin and lignin. Survival of golden perch, Macquaria ambigua, larvae in aquaria treated with a simulated annual litter density of 450 g m−2 for 72 h was 14·9% for 15‐day‐old larvae and 0% for 8‐day‐old larvae. A litter density of 1223 g m−2 resulted in total mortality for both age groups of larvae. Aeration increased survival of larvae to a minimum of 68·8% in 1223 g m−2 litter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Endosulfan, chlorpyrifos, and phenol were supplied by Hoechst Australia, Dow Elanco Australia, and Rhone Pouline Laboratory Products, Australia, respectively. Endosulfan and chlorpyrifos are widely used agricultural pesticides, and phenol is a naturally found component in urban and country rainwater in Australia as a result of leachate from vegetation [22]. Fish maintenance, acclimatization, and CTM tests were carried out in dechlorinated bore water, passed through two sets of filters including an activated carbon filter prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Endosulfan, chlorpyrifos, and phenol were supplied by Hoechst Australia, Dow Elanco Australia, and Rhone Pouline Laboratory Products, Australia, respectively. Endosulfan and chlorpyrifos are widely used agricultural pesticides, and phenol is a naturally found component in urban and country rainwater in Australia as a result of leachate from vegetation [22]. Fish maintenance, acclimatization, and CTM tests were carried out in dechlorinated bore water, passed through two sets of filters including an activated carbon filter prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Fish kills caused by hypoxic blackwater have been recorded several times in different aquatic habitats across Australia, including in the Murray Valley (see for example Gehrke et al 1993;McKinnon and Shepheard 1995;Baldwin et al 2001;Townsend and Edwards 2003;Baldwin and Whitworth 2009). Although relatively few fish were actually reported dead during this event (Allan Lugg, pers.…”
Section: Impacts On Fishmentioning
confidence: 98%
“…Hypoxic blackwater events have been attributed to several fish kills in Australia (e.g. Gehrke et al 1993;McKinnon and Shepheard 1995;Baldwin et al 2001;Townsend and Edwards 2003;Baldwin and Whitworth 2009) and emergence (and sometimes mortality) of large crustaceans, such as the Murray crayfish (Euastacus armatus) (McKinnon 1995). However, McNeil and Closs (2007) also demonstrated that several fish in floodplain wetlands have high tolerances to hypoxia, and are able to avoid or tolerate hypoxic conditions by surface respiration.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…During extended droughts, hypoxic episodes may occur frequently in isolated floodplain lentic waterbodies (billabongs), particularly where water temperature is high (Gehrke, 1991;Lake, 2003). For the majority of the Australian inland fish fauna very little is known about their distribution in hypoxic habitats and even less about the mechanisms and adaptations used for surviving hypoxic episodes (Gehrke, 1991;Townsend, Boland & Wrigley, 1992;Gehrke, Revell & Philby, 1993;Closs & Lake, 1996;King, Humphries & Lake, 2003).…”
Section: Introductionmentioning
confidence: 99%